Economy and Society: Essays on Interpretive Sociology (an excerpt) - Max Weber (Journal of Economic Sociology, 2016)
This book is the first Russian translation of the first volume of Max Weber’s classic work Economy and Society. Volume I uncovers the methodology of Max Weber’s interpretive sociology in general. This volume defines the fundamental concepts of sociology, describes the main principles of economic sociology, explains statements about the sociology of power, and indicates directions for the development of social stratification. Therefore, the volume provides readers with systemized tools and a specific lens for understanding issues, which social sciences generally care about, that are discussed in the following volumes of this outstanding work.Journal of Economic Sociology has published a short excerpt from the first chapter, “The fundamental Concepts of Sociology,” from Volume I, Sociology. This chapter presents a program for interpretive sociology, including its substantial and methodic fundamentals. The chapter also indicates how sociology is related to similar disciplines. Social action is key for understanding sociology.